Odorant-binding protein from the stable fly (Stomoxys calcitrans) has a high-histidine N-terminal extension that binds transition metals. (February 2022) - Shah, Jaee Shailesh; Buckmeier, Beverly Greta; Griffith, Wendell; Olafson, Pia Untalan; Perez de Leon, Adalberto A.; Renthal, Robert
Abstract: The role of odorant- and pheromone-binding proteins (OBPs) in olfactory function is not fully understood. We found an OBP sequence from the stable fly, Stomoxys calcitrans, ScalOBP60, that has a 25 amino acid N-terminal extension with a high content of histidine and acidic amino acids, suggesting a possible metal binding activity. A search of public databases revealed a large number of other fly OBPs with histidine-rich N-terminal extensions, as well as beetle, wasp and ant OBPs with histidine-rich C-terminal extensions. We recombinantly expressed ScalOBP60, as well as a truncated sequence which lacks the histidine-rich N-terminal region, tScalOBP60. Using fluorescence quenching and electrospray quadrupole time-of-flight mass spectrometry (ESI-QTOF), we detected two different types of metal-binding sites. Divalent copper, nickel and zinc bind to the N-terminal histidine-rich region, and divalent copper binds to an internal sequence position. Comparison of the ESI-QTOF spectra of ScalOBP60 and tScalOBP60 showed that the histidine-rich sequence is structurally disordered, but it becomes more ordered in the presence of divalent metal. When copper is bound to the internal site, binding of a hydrophobic ligand to ScalOBP60 is inhibited. The internal and N-terminal metal sites interact allosterically, possibly through a conformational equilibrium, suggesting a mechanism for metal regulation of ligand binding to ScalOBP60. Based on our studies of ScalOBP60, we propose several possible olfactory and non-olfactory functions for this OBP. Graphical abstract: Image 1 Highlights: Many insect odorant-binding proteins have histidine-rich N- or C-terminal sequences. Stable fly His-rich odorant-binding protein ScalOBP60 binds Cu 2+, Zn 2+, and Ni 2+ . Truncated ScalOBP60, lacking histidine-rich sequence, binds Cu 2+ . Cu 2+ bound to truncated ScalOBP60 inhibits hydrophobic ligand binding. Model proposed for metal ion regulation of hydrophobic ligand binding to ScalOBP60.